Efeitos do plasma de baixa temperatura sobre os substratos esmalte e dentina - Alves, Roberto Haniery Ponte (2015)
Low-temperature plasma (LTP) is a promising technology with the potential benefit of destroying the matrix of the oral biofilm and also produce antimicrobial effect on the bacterial cell. However, the effect of LTP on dental structures is not clear. The objective of this study was to evaluate the effect of LTP on enamel and dentin substrates. Therefore, we analyzed Knoop microhardness to calculate the percentage of surface hardness (SH), changes in contact angles (CA), the surface topography by Scanning Electron Microscopy (SEM) and also the chemical composition by Raman spectrometry (RS). Initially, 4x4x2 mm enamel and dentin blocks were prepared from bovine incisors. All blocks were polished and divided into three groups (n = 6); argon plasma, argon flow rate and control. The SH was assessed before and after each treatment, performing five penetrations in each specimen (50g / 25g and 5s enamel / dentin 5s). Contact angles changes were performed by dispersing water drop on the treated surfaces and observing the contact angle obtained after 1 min and 1 hour. For that, high-resolution digital photos and the Image J program was used. Physical changes in the structure of enamel and dentin submitted to LTP were observed from the SEM. Additionally, the relative proportion of the organic and mineral content of the enamel and dentin after treatment were analyzed by RS. Data were evaluated by analysis of variance (ANOVA) - 2-way (treatment and time) and Tukey test (α <0.05). For the SH the results showed no significant difference in the enamel (p=0.087), however, the SH of dentin decreased after treatment with argon plasma (p=0.005). The results indicated that water contact angle values in enamel decreased after 1min of the application of argon plasma (p<0.05). In the dentin the contact angle decreased after 1 and 60 min of the application of argon plasma (p<0.05). The RS results showed than argon plasma and argon gas presented lower organic matrix bands, similar results were observated for both enamel and dentin. The SEM showed that in addition to removing the external smear layer to the dentinal tubules, treatment with LTP promoted cracks in the enamel and the dentin surfaces. In conclusion, the use of argon plasma decreased the superficial hardness in dentin and, potentially increased the wetting in booth substract. Superficial morphological change and decreased of the organic matrix were observed in booth estructures after treatment with argon plasma and argon flow rate.